Cost and size optimization of solar photovoltaic and fuel cell based integrated energy system for un-electrified village. (December 2017) - Khemariya, Manish; Mittal, Arvind; Baredar, Prashant; Singh, Anand
Highlights: Solar PV and PEM Fuel cell based Integrated Energy System. Integrated energy system for un-electrified village. Average electrical production from the PV array and fuel cell. A Solar PV-Fuel Cell IES has been proposed for Jhiriya-Kheda village. Abstract: The main aim of designing any energy system is to ensure that maximum energy is generated with minimum capital investment. Also, the cost associated with generating electricity from the system should also be minimum. In order to achieve these aims, integrated energy systems are to be designed and optimized in such a way that the best possible sizing of the components is obtained upon cost and other constraints. This paper gives the details of a solar photovoltaic (PV) and proton exchange membrane (PEM) fuel cell based integrated energy system (IES) proposed in an Indian village. The estimation of the expected load profile of the village and optimization of the system is done using hybrid optimization model for electrical renewable (HOMER) software. The framework adopted for the optimization, the results obtained after simulation and their analysis have been included in detail.